Brentuximab vedotin as a bridge to combination chemotherapy in gray zone lymphoma with severe liver impairment: a case report - Asrani, Roshan; Cengiz, Turgot Bora; Petersen, Bruce E.; Anagnostou, Theodora; Brody, Joshua D. (Frontiers in Oncology, 2024)
Background: Gray zone lymphoma (GZL) is a rare lymphoma subtype characterized by features intermediate between diffuse large B-cell lymphoma (DLBCL) and classic Hodgkin lymphoma (cHL). The optimal first-line treatment for GZL remains undefined, particularly for patients with poor performance status or baseline organ impairment. Brentuximab vedotin (BV), a targeted therapy that binds to CD30, a TNFR superfamily member involved in NF-kB signaling, has shown promise in the treatment of CD30-positive lymphomas. However, its use in GZL, especially in patients with severe liver impairment, has not been reported previously.Case Description: We present a case of a 37-year-old male with GZL and severe liver impairment at initial presentation. The patient initially received monotherapy with BV, which resulted in a marked improvement in liver enzymes and bilirubin levels. Subsequently, combination cytotoxic chemotherapy consisting of dose-adjusted etoposide, prednisone, cyclophosphamide, and doxorubicin (DA-EP_CH) was added. Repeat imaging revealed near complete resolution of lymphadenopathy and significant reduction in hepatosplenomegaly. The patient completed a full course of chemotherapy and achieved a complete response. Follow-up examinations showed no evidence of recurrent disease, and the patient resumed full-time work.Discussion: GZL poses diagnostic challenges due to its overlapping features with DLBCL and cHL. Accurate diagnosis relies on comprehensive histopathological evaluation, immunophenotyping, and molecular analysis. The optimal first-line treatment for GZL remains uncertain. BV shows promise as an addition to chemotherapy in GZL, even in the presence of severe liver impairment. The molecular pathogenesis of GZL is complex and heterogeneous, frequently involving aberrant NF-kB signaling and impaired apoptosis regulation via loss of TP53 expression. Understanding the underlying molecular mechanisms is essential for developing targeted therapies and identifying predictive biomarkers for treatment response.This case demonstrates the successful use of BV as a bridge to cytotoxic chemotherapy in a GZL patient with severe liver impairment, highlighting its potential safety and efficacy even in the setting of end-organ failure. Further investigation is warranted to define optimal treatment strategies, identify predictive biomarkers, and improve outcomes for patients with this rare and challenging lymphoma subtype.